Determine Key Purchase Decision Factor Farmer in Rice Selective Herbicide - Tirtana Hariyono, Ardian; Nasiron, Nasiron; Labib, M.; Riyanto, Dimas (Green Publisher, 2023)
Rice yield potential in average still below achievement. Weed control process in rice cultivation one of key driver to increase yield and selective herbicide application adoption become main factor. There is indication rice farmer have low adoption to application rice selective herbicide. The purpose of this study to get clarifiy from farmer perspective regarding purchase decision factors for rice selective herbicide of farmers perspective. The method of this research use qualitative methods by study case approach with in-depth interview (IDI), focus group discussion (FGD) and composite performance index (CPI) among five rice key farmers as informants. The result of this study are price is main purchase decision factor of rice selective herbicide product compare quality, time and flexibility application. Promotion activity that conducted by private sector play important role in determining key buying decision factors in rice selective herbicide.